2011
DOI: 10.1093/ecam/nep151
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Anti‐inflammatory Effects of a Kampo (Japanese Herbal) Medicine “Shoseiryuto (Xiao‐Qing‐Long‐Tang)” on Airway Inflammation in a Mouse Model

Abstract: Effects of a Kampo (Japanese herbal) medicine “shoseiryuto (SST, xiao-qing-long-tang in Chinese)”, which has been used for the treatment of allergic bronchial asthma clinically, were examined on ovalbumin (OVA)-sensitized allergic airway inflammation model (i.e., bronchial asthma) in a mouse. When SST was orally administered at 0.5 g kg−1 day−1 from day 1 to 6 after OVA inhalation, SST reduced the inflammation in lung tissue, the number of eosinophils and the OVA-specific immunoglobulin E (IgE) antibody titer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Xiao-QingLong-Tang (XQLT) contains eight herbal complexes and has been commonly used for the clinical treatment of bronchial asthma and allergic rhinitis in Asia (Kung et al, 2006;Nagai et al, 2009). Recently, investigators demonstrated that XQLT improved the quality of life and reduced the symptoms of illness in common cold patients (Byun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Xiao-QingLong-Tang (XQLT) contains eight herbal complexes and has been commonly used for the clinical treatment of bronchial asthma and allergic rhinitis in Asia (Kung et al, 2006;Nagai et al, 2009). Recently, investigators demonstrated that XQLT improved the quality of life and reduced the symptoms of illness in common cold patients (Byun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Xiao-Qing-Long-Tang (XQLT) is the second most commonly used HF for asthmatic children, and it has extensive effects on decreasing Th2-related immune response, anti-inflammatory, reducing secretion, and has potent bronchodilator effect [25, 26, 3436]. Also, it is effective in controlling allergic rhinitis [37].…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional electrophoresis was performed according to the procedure given by Oh-Ishi et al [10][11][12][13].…”
Section: Agarose 2-d Electrophoresismentioning
confidence: 99%